Influence of socioeconomic factors on the perception of cochlear-vestibular symptoms and adherence to the treatment of congenital hypothyroidism - Gabriela Carvalho Machado; Caio Leônidas Oliveira Andrade; Ingrid Sampaio Souza; Luan Paulo Franco Magalhães; Luciene da Cruz Fernandes
Abstract Objectives: to verify if there is an association between socioeconomic factors and adherence to treatment in congenital hypothyroidism and to verify if there is an association between socioeconomic factors and vestibulocochlear symptoms noticed by parents/caregivers of children diagnosed with congenital hypothyroidism. Methods: a cross-sectional, exploratory and descriptive study, with a convenience sample. The sample consisted of 108 children with clinical and laboratory diagnosis of congenital hypothyroidism, of both sexes, aged ≥ 5 years. The researchers applied a structured questionnaire to parents/caregivers, consisting of closed and objective questions about the presence or absence of tinnitus, hearing loss and dizziness/vertigo in children with congenital hypothyroidism. Results: There was no association between socioeconomic factors and adherence to treatment or perception of cochlear-vestibular symptoms. Conclusions: socioeconomic factors did not influence treatment adherence or perceived cochlear-vestibular symptoms by caregivers of children with congenital hypothyroidism.